MANAJEMEN WAKTU SANTRI DI DAYAH TAHFIDZ ULUMUL QUR’AN PAGAR AIR BANDA ACEH - Fudhailul Barri (Jurnal Ilmiah Didaktika, 2016)
Time management is a planning, organizing and monitoring productivity of time. The time becomes one of the resources of performance that must be managed effectively and efficiently. In education, the time is like a sword that must be mastered, as well as in the field of Tahfidz al-Qur’an, one of which is applied in Dayah Tahfidz Qur’an Pagar Air Banda Aceh, management is needed in order to achieve the target. This study attempted to answer about the concept of time management, applications, settings, and their implications to students.This research was a field study using a qualitative approach, conducted in Dayah Tahfidz Pagar Air Banda Aceh. The techniques of collecting data were interview, observation and documentation. The data analysis technique is done through data reduction, data presentation and verification of data.The results showed that the concept of time management in the Dayah Tahfidz Pagar Air was designed with the model, after Magrib prayer and Isya’ and ba'da Subuh prayer. That time includes a brief, if the priority of Dayah devoted to tahfidz. Time management was not implemented maximally, students were often procrastinate, less recognize activities (tahfidz) application time do still less strict. In addition, students concentrate less on the results, as well as the response or attitude that is still less strict on time. Time management implications of the recitation of the Koran in Dayah Tahfidz Ulumul Qur'an Pagar Air Banda Aceh, in general, can be seen from the increase and change of students in memorizing al-Qu'ran.